Image Patterns In Webster's Duchess of Malfi and White Devil - Gray, V. M. (My University, 1970)
The aim of this paper is to prove that there is a pattern in Webster’s use of imagery, at least in the two great plays.
Keywords: Plays; Webster; Duchess of Malfi; John Webster; Theater; Theatre; White devil; Playwright; Stage; tragedies